2014
DOI: 10.2340/16501977-1239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a stroke-specific follow-up care model on the quality of life of stroke patients and caregivers: A controlled trial

Abstract: The intervention was not effective in improving quality of life, but was effective in improving levels of social activities. The intervention may have focussed too much on screening for stroke-related problems and not as much on adequate follow-up care and referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 22 publications
1
43
1
1
Order By: Relevance
“…9,10,13,14,17,18 One large study used cluster randomization by unit. 11 The remaining three studies were quasi-experimental (e.g., non-random assignment to condition 12,16 or single group 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,13,14,17,18 One large study used cluster randomization by unit. 11 The remaining three studies were quasi-experimental (e.g., non-random assignment to condition 12,16 or single group 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…19 Small pilot studies are useful in testing feasibility of recruitment, retention, and implementation of the intervention, among other procedures; however, intervention effectiveness cannot be adequately determined in these studies. 19 Four studies 9,13,16,18 had moderate sample sizes ranging N=119 16 to N=254, 9 and one study was quite large (N=928). 11 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCM is based on six essential elements that are fundamental to effective partnerships between informed, activated patients and prepared, proactive practice teams: 1) community resources and policies; 2) health care organization; 3) self-management support; 4) delivery system design; 5) decision support; and 6) clinical information systems. However, the focus of chronic care management is often centred on the management of single diseases for individuals rather than on the provision of population-based, comprehensive and integrated health and social care services for people with multiple conditions and their families [11011121314]. In this study we use the CCM to understand and characterize the delivery of ICBPHC.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of stroke follow-up care unexpectedly showed that the intervention reduced carer depression but did not affect patient outcomes. 6 Conversely, a trial of reminiscence therapy for dementia concluded that though quality of life may have improved for people with dementia who attended the sessions, carers' anxiety increased significantly. 7 Other interventions, such as the closure of mental health beds or the promotion of activity among frail older people, could also benefit patients at the expense of carers.…”
Section: Fig 1 How Patient Interventions Can Affect Carer Outcomesmentioning
confidence: 99%